Character and moral education based learning in students’ character development - Indah Suciati; Idrus Idrus; Hajerina Hajerina; Nasim Taha; Dewi Sri Wahyuni (International Journal of Evaluation and Research in Education (IJERE), 2023)
Internet-based learning is mostly done because of the industrial revolution and COVID-19 so it has an impact on shifting the students’ character. The systematic literature review research purpose was to analyze and provide an overview related to learning based on character and moral education in the student’s character development. Data related to character and moral education (2020-2022) was collected through the Indonesian National Library and Google Scholar for documentation which will then be reviewed. After the screening, 25 articles were selected for analysis using the Miles & Huberman interactive model and thematic analysis to obtain answers to review questions. These findings provided information about various methodologies and research results related to the student’s character and moral education. The results showed that students’ moral character development was influential and related to learning outcomes, self-character, and performance, as well as contributing to students’ mental health. So that efforts can be made in developing and strengthening student character through internal education strategies, such as material content containing character values, local wisdom-based learning, as well as the use of character-based learning models, methods and media, and external strategies in the form of parental support and society.